Membongkar Paradigma Positivisme Hukum dalam Pemberantasan Korupsi di Indonesia: Pemenuhan Hak Asasi Manusia dalam Negara Hukum - Habib Shulton Asnawi (UIN Sunan Kalijaga Yogyakarta, 2013)
Thinking in this paper, motivated by concerns about increasing corruption cases in Indonesia, both central to the regional level. This is due to law enforcement (Judges, Prosecutors and Police) in Indonesia is still dominated by the paradigm and way of thinking